biografiA. Lexikon österreichischer Frauen, Band 1 Band 01, A-H - Korotin, Ilse (c5252310-e860-4b48-8274-72cda7597ca0, 2016)
biografiA gives on the basis of selected 6.367 biographies an overview over many centuries of austrian female history and various insights into the cultural and social contexts of the concerned eras both for experts and the interested public.